Micro-Computed Tomography and Finite Element Method Study of Open-Cell Porous Materials - Wejrzanowski Tomasz; Skibinski Jakub; Cwieka Karol; Kurzydlowski Krzysztof J. (MATEC Web of Conferences, 2015)
In the present paper the characterization of structure and properties of open-cell porous materials by high-resolution x-ray micro-computed tomography (μCT) and finite element method (FEM) is addressed. The unique properties of open porosity foams make them interesting in a range of applications in science and engineering such as energy absorbers, lightweight construction materials or heat insulators. Consequently, a detailed knowledge of structure as well as mechanical properties (i.e. Young’s Modulus, Poisson’s Ratio) of such foams is essential. The resulting pixel size of the μCT was 40 μm, which enabled satisfactory visualization of the complex foam structure and quantitative characterization. Foam morphology was studied on post-processed computed tomography images, while mechanical properties were analyzed with use of the finite element method on numerical model obtained from μCT results.